1981
DOI: 10.2307/1912512
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Costs and Labor Supply

Abstract: This study is a theoretical and empirical analysis of the effects of time and money costs of labor market participation on married women's supply behavior. The existence of fixed costs implies that individuals are not willing to work less than some minimum number of hours, termed reservation hours. 'The theoretical analysis of the properties of the reservation hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
7

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(115 citation statements)
references
References 5 publications
4
104
0
7
Order By: Relevance
“…The sample we utilize excludes two-parent households since our model of demand for irregular commodities does not take i n to account interactions between members within the household. 6 The sample includes 1 569 individuals of which 236 that is, 15 purchased irregular commodities in 1993 see the last line of Table 1 . The average total purchases of irregular commodities by individuals who did not work in the underground sector 1 440 individuals is $136 Can , while it amounts to $817 for the 129 individuals who worked in the underground sector see columns 1 and 2 .…”
Section: The Survey and Descriptive Resultsmentioning
confidence: 99%
“…The sample we utilize excludes two-parent households since our model of demand for irregular commodities does not take i n to account interactions between members within the household. 6 The sample includes 1 569 individuals of which 236 that is, 15 purchased irregular commodities in 1993 see the last line of Table 1 . The average total purchases of irregular commodities by individuals who did not work in the underground sector 1 440 individuals is $136 Can , while it amounts to $817 for the 129 individuals who worked in the underground sector see columns 1 and 2 .…”
Section: The Survey and Descriptive Resultsmentioning
confidence: 99%
“…Bourguignon and Magnac (1990) estimate a model for women that includes fixed costs and find that the uncompensated labour supply elasticity is reduced from 0.96 to 0.39. Cogan (1981) finds that the uncompensated labour supply elasticity falls from 2.45 to 0.88 after correcting for entry costs.…”
Section: The Empirical Literature On Labour Supply Elasticitiesmentioning
confidence: 97%
“…While these characteristics are also observed for non-workers, wages can be imputed for non-workers by using the estimated coefficients of the regression. Studies that explicitly take into account selection are Cogan (1981); Mroz (1987); Arellano and Meghir (1992); Blundell et al (1998) and Devereux (2004). Mroz explicitly tests for different selection models and rejects the Tobit model for more general models that allow different specifications for participation and labour supply.…”
Section: The Empirical Literature On Labour Supply Elasticitiesmentioning
confidence: 99%
“…Although such a dataset is not readily obtainable, Thorat and Attewell (2007), as an exception, collected a dataset of (hypothetical) job applicants by sending different types of applications to several job offers placed in newspaper advertisements and examined the existence of "job discrimination." 5 For the studies on transaction costs associated with entry into the market, see, for instance, Cogan (1981) on married women's labor supply in the U.S., and Sadoulet et al (1998) and Key et al (2000) on corn producers' supply responses to labor and product markets in Mexico. These studies found that transaction costs matter for workers' or households' decisions on market involvement.…”
Section: Introductionmentioning
confidence: 99%